Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SD Negeri Perumnas Kecamatan Rappocini Kota Makassar - Supriadi; Mas’adi; Roberto Rolly Bulalong; Muslim AR (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
This study examines the Implementation of the Numbered Heads Together (NHT) Cooperative Learning Model to improve social studies learning outcomes in fourth grade students of Perumnas Public Elementary School, Rappocini District, Makassar City. The approach used is a qualitative approach with the type of research in the form of classroom action research. The research setting took place at Perumnas Public Elementary School, Rappocini District, Makassar City with research subjects consisting of one teacher and 30 fourth grade students of Perumnas Public Elementary School. Data collection used observation, tests, and documentation, while data analysis used descriptive qualitative analysis. The results of this study indicate that the implementation of the Numbered Heads Together cooperative learning model can increase teacher and student activity in learning so that learning outcomes increase. This increase can be seen from the score of students' social studies learning outcomes in each cycle, namely in cycle I it is in the sufficient category with details of 30 fourth grade students, there are 12 students who meet the minimum completeness criteria which is 70 with a percentage of 40%, and 18 students who have not met the minimum completeness criteria with a percentage of 60%. Meanwhile, the results of students' social studies learning in cycle II were in the very good category and experienced an increase with details of 30 grade IV students, there were 26 students who met the minimum completion criteria with a percentage of 86.67%, and 4 students who had not met the minimum completion criteria (KKM) with a percentage of 13.33%. So it can be concluded that learning with the application of the NHT type cooperative model can improve the results of social studies learning of grade IV students of Perumnas Elementary School, Rappocini District, Makassar City.